What might 'just green enough' urban development mean in the context of climate change adaptation? The case of urban greenspace planning in Taipei Metropolis, Taiwan. (July 2018) - Mabon, Leslie; Shih, Wan-Yu
Highlights: Climate adaptation needs reconsideration of equity in urban greening, as ecosystem function comes from range of greenspaces. Risk of reinforcing inequality via structural issues in planning processes must be balanced with risk of harm from inaction. In Taipei, site-specific controversies about greenspace in urban development challenge evidence-based adaptation planning. Taipei illustrates how excessive pragmatism towards how greening is achieved may sideline or obscure justice concerns. Taipei suggests scientific and political competences required for strategic greening make equity planning more complex. Abstract: This paper argues that climate change adaptation through strategic greenspace planning requires scholars and planners to think differently about what equity means in an urban greenspace context. We use the heat mitigation potential of greenspace and the case of Taipei Metropolis in Taiwan to assess challenges arising from thinking about fairness in terms of distribution of benefits from greenspace functions, as opposed to fairness in greenspace accessibility and availability. Urban greening to foster 'resilient' communities arguably deflects from – or even exacerbates – structural causes of vulnerability, with benefits accruing disproportionately to more affluent or empowered groups. Yet the need for practical action on climate threats in cities is urgent, and for heat, strategic greenspace use considered systematically across a city may mitigate effects through the cooling effect of vegetation. The challenge is thus to balance the justice concerns associated with urban greening with this tangible risk reduction potential. We undertake content analysis of articles from two Taiwanese newspapers – the Taipei Times and the China Post – to assess how heat and greenspace issues have been discussed in urban governance debates within Taipei. We suggest change adaptation through urban greening raises three challenges for equity thinking: (a) guiding planning and governance processes with scientific understanding of how greenspace functions are delivered, even in the face of urban development pressures and site-specific controversies; (b) tempering the social cohesion and practical deployment benefits of neighbourhood-level greening with the need for specific understanding at the city-wide level to most effectively realise ecosystem services; and (c) linking targeted adaptation actions with broader rationales for urban greening, whilst not diluting justice concerns. We caution that pragmatism towards all urban climate adaptation via greening as intrinsically 'good' must not serve as a blinder to the need for accompanying social policy measures to reduce unequal vulnerability to climate risks.